2018
DOI: 10.1007/s10723-018-9442-6
|View full text |Cite
|
Sign up to set email alerts
|

A Dynamic Profile Questions Approach to Mitigate Impersonation in Online Examinations

Abstract: Online examinations are an integral component of many online learning environments, which face many security challenges. Collusion is seen as a major security threat to such examinations, when a student invites a third party to impersonate or abet in a test. This work aims to strengthen the authentication of students via the use of dynamic profile questions. The study reported in this paper involved 31 online participants from five countries over a five-week period. The results of usability and security analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 26 publications
0
22
0
3
Order By: Relevance
“…From previous researches, we found that it is very important to find a way to evaluate authentications for various platform's policies [9,10,29]. The evaluation criteria are built based on a combination of three parts: password intensity, guessability percentage rate, and entropy measurement.…”
Section: Knowledge-based Authentication Security Measurementsmentioning
confidence: 99%
“…From previous researches, we found that it is very important to find a way to evaluate authentications for various platform's policies [9,10,29]. The evaluation criteria are built based on a combination of three parts: password intensity, guessability percentage rate, and entropy measurement.…”
Section: Knowledge-based Authentication Security Measurementsmentioning
confidence: 99%
“…The focus and research context of this work relates to summative assessment or remote online examinations. The growth in the use of online learning in higher education has been documented and reported in many studies [5], [6], [7], [8], [9]. It has attracted significant research focus on developing and delivering secure, efficient and effective learning environments.…”
Section: Introductionmentioning
confidence: 99%
“…In a similar vein, the use of image-based questions revealed improved usability [13], however, these questions were not sufficient to mitigate impersonation and abetting. In order to address the security issues, the authors proposed dynamic profile questions [7]. These questions are created in the background when a student performs learning activities.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations